Langer-Giedion Syndrome with 8q23.1–q24.13 Deletion by Complex Three-way Translocation - Min, Sunghee; Seo, Eul-Ju; Seol, Chang Ahn; Kim, Gu-Hwan; Lee, Beom Hee; Lee, Dong-hyun (Laboratory Medicine Online, 2018)
Langer–Giedion syndrome is a very rare genetic disorder that is caused by the deletion on chromosome 8q24.1, encompassing the TRPS1 and EXT1 genes. We describe a 5-month-old female patient who was admitted to our hospital with clinodactyly and weakness in both thumbs. The patient’s karyotype was 46,XX,der(4)t(4;19)(q27;q11),der(8)t(4;8)(q27;q22.3),der(19)t(8;19)(q22.3;q11)del(8)(q23q24.1). Multiplex ligation-dependent probe amplification (MLPA) analysis showed that the patient had a heterozygous deletion, rsa 8q24(P064)x1 and rsa 8q24(P245)x1. Array comparative genomic hybridization (CGH) analysis further revealed three interstitial deletions spanning a total of 13.7 Mb at 8q23.1–q24.13. Based on clinical findings and confirmation by cytogenetic, MLPA, and array CGH analyses, the patient was diagnosed with sporadic Langer–Giedion syndrome with three-way translocations. This is the first case of Langer–Giedion syndrome with complex chromosomal rearrangements in Korea. KCI Citation Count: 0